2010
DOI: 10.1186/1471-2458-10-492
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of physical disability and functional limitation among community dwelling older people in rural Malaysia, a middle income country

Abstract: BackgroundThe prevalence and correlates of physical disability and functional limitation among older people have been studied in many developed countries but not in a middle income country such as Malaysia. The present study investigated the epidemiology of physical disability and functional limitation among older people in Malaysia and compares findings to other countries.MethodsA population-based cross sectional study was conducted in Alor Gajah, Malacca. Seven hundred and sixty five older people aged 60 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
73
2
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(101 citation statements)
references
References 37 publications
22
73
2
4
Order By: Relevance
“…Hairi et al showed that advancing age was significantly associated with functional limitation [35]. We did not find significant correlation between disability and income, however, a study done ona random sample of persons, 55-85 years of age, drawn from the population registers of 11 municipalities found that low socioeconomic status had been associated with physical disability [36].…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Hairi et al showed that advancing age was significantly associated with functional limitation [35]. We did not find significant correlation between disability and income, however, a study done ona random sample of persons, 55-85 years of age, drawn from the population registers of 11 municipalities found that low socioeconomic status had been associated with physical disability [36].…”
Section: Discussioncontrasting
confidence: 61%
“…Bergamini et al found that older Italian men and women showed similar prevalence of functional limitation, 31% and 28%, respectively [37]. However, Hairi et al found that female gender was significantly associated with functional limitation; they suggested that disadvantages resulting from limited education may contribute to the greater physical disability and functional limitation burden experienced by older women in their study [35].…”
Section: Discussionmentioning
confidence: 87%
“…Female gender and older age appear on a recurring basis as risk factors for functional disability in the majority of studies 16,19,20 and the present study is no exception. Women have a higher life expectancy than men and pass a greater proportion of their life with functional disability; moreover, when affected by this condition, they live for a longer period with dependency 21 .…”
Section: Discussionsupporting
confidence: 49%
“…Even among HIV infected populations in South Africa, older women were still at a higher risk of disabilities compared to older men [13]. Studies in middle income countries have also reported increased disability among older women [14] [15]. In developed countries like USA, older women were also disadvantaged in terms of the prevalence of disability [16].…”
Section: Older Persons and Disabilitymentioning
confidence: 98%